Orientation of Urban Women's to Support The Implementation of Global Indonesia Climate Change; A Comparative Study of Bandar Lampung And Bogor - Tampubolon, Novelina; Avenzora, Ricky; Hermawan, Rachmad (Media Konservasi, 2018)
Increasing women's participation in supporting climate change improvement is considered important where women's activities are very close to the environment. The cities of Bandar Lampung and Bogor have been identified as being no longer comfortable so that they are potentially used as research sites to analyze the potential of women's participatory funds that are potentially available in Indonesia. The objectives of this study are: 1) to analyze the comparison of perceptions of women in Bandar Lampung City and Bogor City against global climate change and 2) to analyze the comparison of women WTP values in Bandar Lampung City and Bogor City to participate in improving the global climate. Data were taken using closed ended questionnaires, then analyzed by Kruskal Wallis and Dunn Test, T Test and Z Test. The results of the study showed that according to Bandar Lampung City women that reduced RTH was the main problem causing a decrease in environmental quality. Unlike Bogor City women who perceive that population growth is the main cause of the decline in environmental quality. In addition, women in Bandar Lampung City perceive that the increase in temperature and humidity in their area is higher than that of Bogor City. The results of the comparison of WTP values show no significant difference where Bandar Lampung City is Rp. 12.429 / KK / month and Kota Bogor is Rp. 10.226 / KK / month; cumulatively the potential for women's participation in Bandar Lampung City is Rp. 35.025.618.024 per year and in Bogor City Rp.32.138.027.376 per year. Keywords: Climate change, community participation fund, Willingness To Pay (WTP), women’s orientation